دراسة العوامل المؤثرة على استخدام نظم المعلومات الإدارية في قطاع الخدمات باستخدام التحليل العاملي - تطبيق على بعض المؤسسات العامة والخاصة - عربش, شفيق; عباس, فداء علي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
حاولنا في هذا البحث دراسة عدة مقاييس لمعرفة أثرها على استخدام نظم المعلومات الإدارية في المؤسسات الخدمية وذلك باستخدام أسلوب التحليل الإحصائي متعدد المتغيرات المتمثل بأسلوب التحليل العاملي، الذي يساعد في تخفيض المتغيرات إلى عدد أقل على شكل تصنيف جديد من العوامل. يتضمن هذا البحث نظم المعلومات الإدارية وأهمية استخدامها في قطاع الخدمات، وقد اعتمدنا على عينة مكونة من 160 استبياناً وزعت على بعض العاملين الإداريين والفنيين متخذي القرار في المؤسسات التي تعمل في القطاع الخدمي ممن يحملون مسميات وظيفية إدارية متمثلة في أربع فئات من المؤسسات الخدمية هي ( المصارف – التعليم – مؤسسات الطيران – التأمين )، ومن ثَمّ تحليل البيانات الواردة من العينة باستخدام الحزمة البرنامجية SPSS، وأهم العوامل التي تؤثر في استخدام نظم المعلومات الإدارية والتي حصلنا عليها من عينة البحث: المركز المالي للمؤسسة - وجود دائرة مستقلة تهتم بهذا الموضوع في الهيكل الإداري للمؤسسة - خبرات ومهارات العاملين. We have tried in this research to study several metrics to determine their impact on the use of management information systems in service institutions using the method of statistical analysis of multivariate factor. This method helps reduce variables to a smaller number in the form of a new classification of factors. This research includes Management Information Systems and it investigates the importance of their use in the Services Sector. We have adopted a sample of 160 Questionnaires distributed to some of the Administrative Staff, Decision Makers, Technicians in the institutions that operate in the Service Sector ( Banks, Education, Airlines foundations and Insurance ). Then, we analyze the data from the research sample using the Package Program SPSS. The most important factors that affect the use of Management Information Systems obtained from the research sample are: the financial position of the institution - the existence of an independent department concerned with this subject in the administrative structure of the institution – and finally the expertise and skills of workers.